THE ROLE OF FOREIGN OWNERSHIP, INSTITUTIONAL OWNERSHIP, INCOME-EARNING ABILITY, AND PROFITABILITY ON COMPANY CAPITAL STRUCTURE DYNAMICS - Juwita, Himmiyatul Amanah Jiwa (Universitas Brawijaya, Indonesia, 2023)
Capital structure is an essential decision for the company. Capital structure is related to the composition and contribution of the company's funding in operational activities. This study aims to identify and describe the variables that affect the company's capital structure. This study uses a quantitative approach with explanatory research. The analysis technique used in this study is to use descriptive analysis and statistical inferential analysis with multiple regression techniques. The population used is a manufacturing company listed on the Indonesia Stock Exchange. The sampling method used is purposive sampling. In this study, the purposive sampling criteria used included Companies that have conducted an IPO (Initial Public Offering) before 2016 and are listed on the Indonesia Stock Exchange and Companies that have published annual financial reports on the IDX from 2016 to 2020. The research variables used are capital structure, company size, profitability, foreign investor ownership, government ownership, and institutional ownership. The research results show that the variables of company income and ownership investors have no significant influence on the dynamics of the company's capital structure. Meanwhile, domestic institutional ownership and company profitability have an influence which is significant to the company's capital structure. There are differences in power, the influence of variables on the company's ability to generate income, investor ownership, and foreign and domestic institutional ownership between companies with share ownership by foreign investors and companies that only have domestic institutions.